IMPLEMENTATION OF ANIMAL WELFARE ON BROILER FARMS IN SEBATU VILLAGE AND TARO VILLAGE, TEGALLALANG SUB-DISTRICT, GIANYAR REGENCY, BALI - Destarani, Putri; Agustina, Kadek Karang; Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2024)
Broiler chickens are the most dominant type of meat consumed by the public. The decline in cattle production could also be influenced by a lack of public knowledge about farm management and lack of knowledge and animal welfare. The aim of the research is to determine the welfare of animals on farms broiler chickens in Sebatu Village and Taro Village, Tegallalang District, Gianyar Regency, Bali. This research uses observational methods. The number of respondents in this study was 10 KK who are raising cattle in Sebatu Village and 10 KK in Taro Village, District Tegallalang, Gianyar Regency, Bali. Gianyar Regency, Bali. in Sebatu Village with a good category reached 40% and very good 60%, while in Taro Village the implementation of animal welfare was good 30% in the good category and 70% in the very good category. It can be concluded that the implementation animal welfare of broiler chickens in the villages of Sebatu and Taro shows that no There are significant differences in the five principles of freedom aspects in animal welfare. It is recommended that farmers continue to improve their understanding and practice of animal welfare.